Development and validation of Japanese version of alternative food neophobia scale (J-FNS-A): association with willingness to eat alternative protein foods - Kamei, Mio; Nishibe, Misaki; Horie, Fuyumi; Kusakabe, Yuko (Frontiers in Nutrition, 2024)
Introduction Food neophobia (FN) is a psychological trait that inhibits one’s willingness to eat unfamiliar foods. It is related to the acceptance of insect foods and cultured meat, which are major protein alternatives to conventional meat, and is an important personality trait for understanding the near-future food industry. However, the factor structure of Pliner and Hobden’s FN scale (FNS) is unstable due to respondents’ cultural backgrounds. Thus, we aimed to develop a Japanese version based on the alternative FNS (FNS-A), the most recent revised version, and to examine its validity. Methods Four online surveys (preliminary 1: n = 202; preliminary 2: n = 207; main: n = 1,079; follow-up: n = 500) were conducted on the FNS-A. For the main survey, Japanese respondents (aged 20–69 years) answered the Japanese version of the FNS-A (J-FNS-A), their willingness to eat (WTE), and their familiarity with hamburgers containing regular protein foods (ground beef, tofu) and alternative protein foods (soy meat, cultured meat, cricket powder, algae powder, and mealworm powder). Results Consistent with the FNS-A, confirmatory factor analysis assuming a two-dimensional structure (approach and avoidance) showed satisfactory model fit indices. The mean J-FNS-A score (Cronbach’s α for 8 items = 0.83) was 4.15 [standard deviation (SD) = 0.93]. J-FNS-A scores were not associated with age and gender, whereas a greater than moderate association was found with WTE hamburgers containing alternative protein foods (rs = −0.42 to −0.33). The strength of these negative associations increased as food familiarity decreased (r = 0.94). The test–retest reliability at 1 month was also satisfactory (r = 0.79). Discussion The validity of the J-FNS-A was confirmed. Higher J-FNS-A scores (mean = 41.51, SD = 9.25, converted to Pliner and Hobden’s FNS score) of the respondents suggest that Japanese people prefer conservative foods. This scale could predict the negative attitudes toward foods with low familiarity, such as alternative proteins. The J-FNS-A appears to be a useful psychological tool for assessing Japanese food neophobia tendencies and predicting novel food choices of Japanese individuals.